Financial Performance and Intellectual Capital Disclosure as Determinants of the Value of Banking Companies with Company Size as Moderating - Ardiantini, Novi; Sukma, Akram Arsyad; Surasni, Ni Ketut (Universitas Pendidikan Ganesha, 2020)
This study aims to analyze the effect of financial performance and intellectual capital disclosure as a determinant of the value of a banking company with company size as a moderator. This type of research is explanatory research. The population in this study amounted to 45 companies in the banking sector listed on the Indonesia Stock Exchange. Sampling was done by purposive sampling with a sample size of 104 companies. The data analysis method used was Moderated Regression Analysis (MRA) with data analysis tools using Eviews version 11. The results show that the variables Return on Equity, Debt to Equity Ratio, and Intellectual Capital Disclosure have a significant positive effect on Price to Book Value and are based on tests. Moderated Regression Analysis shows that the variable company size can moderate the influence of the variables Return on Equity, Debt to Equity Ratio, and Intellectual Capital Disclosure on Price to Book Value.